1992
DOI: 10.1111/j.2042-7158.1992.tb03607.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross-linked Chitosan Microspheres: Preparation and Evaluation as a Matrix for the Controlled Release of Pharmaceuticals

Abstract: Chitosan microspheres having good spherical geometry and a smooth surface were prepared by the glutaraldehyde cross-linking of an aqueous acetic acid dispersion of chitosan in paraffin oil using dioctyl sulphosuccinate as the stabilizing agent. Microspheres having different degrees of swelling were made by varying the cross-linking density. Microspheres were prepared by incorporating theophylline, aspirin or griseofulvin. Drug incorporation efficiencies exceeding 80% could be achieved for these drugs. In-vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
128
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(132 citation statements)
references
References 5 publications
3
128
0
1
Order By: Relevance
“…For example, the drug release rates of theophylline, aspirin and griseofulvin from chitosan microspheres prepared by the emulsion cross-linking of a chitosan solution in paraffin oil as an external medium were influenced by cross-link density, particle size and initial drug loading [116].…”
Section: Influence Of the Preparation Techniques Of Chitin/chitosan-bmentioning
confidence: 99%
“…For example, the drug release rates of theophylline, aspirin and griseofulvin from chitosan microspheres prepared by the emulsion cross-linking of a chitosan solution in paraffin oil as an external medium were influenced by cross-link density, particle size and initial drug loading [116].…”
Section: Influence Of the Preparation Techniques Of Chitin/chitosan-bmentioning
confidence: 99%
“…This problem can be countered by irreversible chemical crosslinking. It has been demonstrated that drug diffusion from chitosan microspheres can be controlled by crosslinking with a dialdehyde such as glutaraldehyde [7].…”
Section: Introductionmentioning
confidence: 99%
“…Determination of melting point of Ziprasidone Hydrochloride Melting point of pure Ziprasidone Hydrochloride was found to be 307 0 C [17] . Identification by thermal analysis (DSC) Melting point of Ziprasidone Hydrochloride was confirmed with its individual DSC thermogram and was found satisfactory [16,18] .…”
Section: Identification Of Ziprasidone Hydrochloride and Chitosanmentioning
confidence: 99%
“…Absorbance of all solutions was measured at 284 nm against distilled water as a blank. The calibration curve was prepared by plotting absorbance versus concentration of drug [16,17] .…”
Section: Identification Of Ziprasidone Hydrochloride and Chitosanmentioning
confidence: 99%